Absorption of Isopropanol on Surface of Defect Silicene - Van On, Vo; Trong Lam, Pham; Van An, Dinh (VNU Journal of Science: Mathematics - Physics, 2020)
In this work, we investigate the defect structure of Silicene with a vancacy and the adsorption mechanism of isopropanol on the surface of defected Silicene by employing the Density Functional Theory method. The adsorption profile was determined based on van der Waals functional optPBE-vdW and the charge transfer between isopropanol and silicene this system was also calculated by Bader charge analysis method. In the defected Silicene, Si vacancy preferably forms on the lower layer of the bulking structure. As a Si vacancy is introduced, Silicene exhibits a metallic behavior with zero bandgap. Due to the losing electron of defected Silicene, isopropanol is adsorbed on the surface with the most favourable adsorption configuration in which oxygen atom towards the surface of Silicene. Isopropanol adsorption opens a tunnelling gap of defected Silicence, resulting in the mili-gap characteristics of the adsorbed Silicene system. The adsorption profile of this volatile organic compound on defected Silicene implies the physics adsorption characteristics. The adsorption energy for isopropanol was found to be -0.40 eV. In addition, the charge transfer of 0.24 electron was obtained